Stable-dreamfusion-gui: a GUI for stable-dreamfusion - Oh, Zhi Hua (Nanyang Technological University, 2023)
Content consumption in the 3D space via Extended Reality Technologies is going to be the future, but 3D content creation remains inaccessible to the masses due to its steep learning curve. With recent developments in the latent diffusion text-to-image models field however, researchers have integrated well trained image generators for use in 3D objects generation, making 3D content creation far more accessible to content creators.